High‐Performance 2D Rhenium Disulfide (ReS2) Transistors and Photodetectors by Oxygen Plasma Treatment. Issue 32 (20th May 2016) - Shim, Jaewoo; Oh, Aely; Kang, Dong‐Ho; Oh, Seyong; Jang, Sung Kyu; Jeon, Jaeho; Jeon, Min Hwan; Kim, Minwoo; Choi, Changhwan; Lee, Jaehyeong; Lee, Sungjoo; Yeom, Geun Young; et al.
Abstract : A high‐performance ReS2 ‐based thin‐film transistor and photodetector with high on/off‐current ratio (10 4 ), high mobility (7.6 cm 2 V −1 s −1 ), high photoresponsivity (2.5 × 10 7 A W −1 ), and fast temporal response (rising and decaying time of 670 ms and 5.6 s, respectively) through O2 plasma treatment is reported.